Michael Psellos on Literature and Art - Psellos, Michael,Barber, Charles,Papaioannou, Stratis (University of Notre Dame Press, 2017)
The ambition of Michael Psellos on Literature and Art is to illustrate an important chapter in the history of Greek literary and art criticism and introduce precisely this aspect of Psellian writing to a wider public. Cover – Michael Psellos on Literature and Art – Title – Copyright – Contents – Note to the Reader – Acknowledgments – Abbreviations – General Introduction – PART ONE. ON LITERATURE: RHETORIC AND ΛΟΓΟΙ – Introduction to Part One – 1 Synopsis of the Rhetorical Forms, based on Hermogenes' On Forms – Translation (in collaboration with Christopher M. Geadrities) – 2 Synopsis of Rhetoric in Verses, based on the Hermogenian Corpus – Translation – 3 On Literary Composition, based on Dionysios of Halikarnassos' On Composition – Translation – 4 On Rhetoric, based on Longinos' Art of Rhetoric – Translation – 5 On Tragedy – Translation – 6 On the Different Styles of Certain Writings: A Rhetor's Canon – Translation – 7 The Styles of Gregory the Theologian, Basil the Great, Chrysostom, and Gregory of Nyssa – Translation – 8 An Encomium of Gregory of Nazianzos' Style – Translation – 9 Two Lectures on Gregory of Nazianzos: Theol. I 19 (on Or. 40.24) and 98 (on Or. 43.1) – Translation – 10 On Saint John Chrysostom – Translation (in collaboration with Christopher M. Geadrities) – 11 To One Asking
Description based on publisher supplied metadata and other sources
Keywords: Aesthetics; Byzantine; Electronic books